Ghana : Tracking Public Resource Flows in Schools and Clinics - World Bank (Washington, DC, 2012)
An accurate estimate of public expenditure flows must start from the distribution and recording systems which would permit accurate tracking. While the strategies to improve these systems in Ghana are beyond the scope of this study, it presents here the problems encountered while trying to track public expenditures. Hopefully, this will provide an entry point for relevant parties to discuss the best ways to increase the efficiency of public expenditure distribution. Estimated resource flows are also presented. Although the accuracy of estimates is not claimed in absolute terms, the patterns of the public expenditure distribution revealed by these estimates were consistent with the perceptions of district level education and health officers, to whom these results were presented at a workshop in Ghana.